2017
DOI: 10.1007/s40799-017-0180-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on Dynamic Tensile Strength and Damage Behavior of Medium-Fine-Grained Huashan Granite

Abstract: In order to investigate the dynamic behavior of medium-fine-grained Huashan granite treated by different temperatures, the splitting tests on the granite specimens are carried out using an improved split Hopkinson pressure bar (SHPB). The dynamic force equilibrium condition in the specimen is basically satisfied. The results show that with increasing treatment temperature, the ultrasonic P-wave velocity decreases, while thermal damage accordingly increases. The damage evolution follows the logistic curve model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Determining the velocity of propagation of elastic waves (acoustic waves) through the material before and after heating is an effective tool for assessing changes in its properties depending on the temperature. e results of a large number of researchers have shown that the propagation velocity of these waves in rocks depends on the mineral composition, density, porosity, microcracks, temperature, and especially the applied pressure [19,42,59,86,87].…”
Section: Evolution Of the Normalized Elastic Wave Velocity Asmentioning
confidence: 99%
See 2 more Smart Citations
“…Determining the velocity of propagation of elastic waves (acoustic waves) through the material before and after heating is an effective tool for assessing changes in its properties depending on the temperature. e results of a large number of researchers have shown that the propagation velocity of these waves in rocks depends on the mineral composition, density, porosity, microcracks, temperature, and especially the applied pressure [19,42,59,86,87].…”
Section: Evolution Of the Normalized Elastic Wave Velocity Asmentioning
confidence: 99%
“…Damage of material is a concept that is increasingly explored and characterizes the state of degradation of this material. In rock engineering, several authors have already expressed their opinions [15,19,22,23,51,65,101,102,[111][112][113][114]. From Figure 10, it can be seen that between 300°C and 500°C, the damage of most rocks is increased continuously [115,116].…”
Section: Thermal Damagementioning
confidence: 99%
See 1 more Smart Citation
“…Rock engineering safety problem induced by high temperature had become an important topic in rock mechanics research [1][2][3]. High-temperature rock mechanical behavior was different from normal temperature, and its physical and mechanical properties were closely related to the temperature; hence, studying the mechanical behavior of rock after high temperature had important theoretical and engineering significance [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have performed many studies on the unique mechanical conditions that rocks experience during the production of geothermal energy. It was found that the dynamic tensile failure strain of rocks increased with increasing temperature [ 10 , 11 ], and the dynamic tensile strength first increased and then decreased by using Brazilian discs to perform dynamic splitting tests of high-temperature rocks [ 12 , 13 ]. Some researchers also carried out studies on the rock surrounding wellbores under a high static load, and it was found that the dynamic tensile strength of the rock under a high static load was far greater than the tensile strength under a static load, and the failure characteristics of tensile strength mentioned above were generally consistent [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%